Albumin, urea-to-albumin ratio, or the albumin-to-creatinine ratio to predict outcomes in heart failure with mildly reduced ejection fraction - Schmitt, Alexander; Akın, Ibrahim; Reinhardt, Marielen; Abel, Noah; Lau, Felix; Dudda, Jonas; Abumayyaleh, Mohammad S. A.; Weidner, Kathrin; Bertsch, Thomas; Dürschmied, Daniel; Behnes, Michael; Schupp, Tobias (European journal of clinical investigation, 2026)
Background This study investigates the prognostic impact of albumin, the urea-to-albumin ratio (UAR), and albumin-to-creatinine ratio (ACR) in patients with heart failure with mildly reduced ejection fraction (HFmrEF), since hypoalbuminemia, renal disease and malnutrition often coincide with heart failure (HF). Methods Consecutive patients hospitalized with HFmrEF at one university medical centre were retrospectively included from 2016 to 2022. Patients were stratified into quartiles based on albumin, the UAR, and ACR. The primary endpoint was all-cause mortality at 30 months (median follow-up), key secondary endpoint was long-term HF-related rehospitalization. Results The study cohort comprised 2,061 patients with HFmrEF with a median albumin level of 32.4 g/L. Albumin levels, the UAR and ACR were predictive for the risk of long-term all-cause mortality, which was still observed after multivariable adjustment (albumin Q1 vs. Q4: HR = 2.260; 95% CI 1.623-3.148; p = .001 / UAR Q4 vs. Q1: HR = 1.507; 95% CI 1.071-2.119; p = .019/ACR Q1 vs. Q4: HR = 2.208; 95% CI 1.528-3.190; p = .001). However, neither albumin nor the UAR or ACR predicted the risk of HF-related rehospitalization (albumin Q1 vs. Q4: HR = 1.117; 95% CI .678-1.842; p = .664 / UAR Q4 vs. Q1: HR = 1.589; 95% CI .922-2.738; p = .095 / ACR Q1 vs. Q4: HR = 1.112; 95% CI .624-1.981; p = .720). Conclusions Hypoalbuminemia is common in hospitalized HFmrEF patients. Low albumin levels, ACRs, and elevated UARs independently predicted long-term all-cause mortality, but not HF-related rehospitalization. The UAR and ACR did not provide a clinically significant predictive advantage over albumin levels alone. Trial Registration ClinicalTrials.gov Identifier: NCT05603390 (date of registration: 10.10.2020)